2021
DOI: 10.3389/fimmu.2021.755624
|View full text |Cite
|
Sign up to set email alerts
|

ERAP, KIR, and HLA-C Profile in Recurrent Implantation Failure

Abstract: The mother’s uterine immune system is dominated by uterine natural killer (NK) cells during the first trimester of pregnancy. These cells express killer cell immunoglobulin-like receptors (KIRs) of inhibitory or activating function. Invading extravillous trophoblast cells express HLA-C molecules, and both maternal and paternal HLA-C allotypes are presented to KIRs. Endoplasmic reticulum aminopeptidase 1 (ERAP1) and 2 (ERAP2) shape the HLA class I immunopeptidome. The ERAPs remove N-terminal residues from antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 70 publications
3
17
0
2
Order By: Relevance
“…Moreover, in all study groups, both mother and fetus had a higher frequency of HLA-C2 compared to the control group [ 32 ]. In our previous study, we showed that the combination of KIR genes from the telomeric region A and HLA-C2C2 in women was associated with infertility and RIF, which confirms our considerations [ 25 ]. Additionally, this work demonstrated the role of the KIR / HLA-C gene system with the ERAP genes in implantation failure.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Moreover, in all study groups, both mother and fetus had a higher frequency of HLA-C2 compared to the control group [ 32 ]. In our previous study, we showed that the combination of KIR genes from the telomeric region A and HLA-C2C2 in women was associated with infertility and RIF, which confirms our considerations [ 25 ]. Additionally, this work demonstrated the role of the KIR / HLA-C gene system with the ERAP genes in implantation failure.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, we did not measure the level of ERAPs in the plasma of men. As we showed in our previous research, the concentration of ERAP2 in women’s plasma was associated with the pregnancy, and high levels of ERAP2 could be related with the miscarriage [ 25 ]. Unlike ERAP1 , the ERAP2 gene shows limited polymorphism.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Among other conditions where associations of ERAP2 presence versus absence were observed, we may also list psoriasis, Crohn’s disease, hypertension, and birdshot chorioretinopathy ( 14 , 17 , 37 ). Similar associations were also described in gynecological diseases: preeclampsia ( 31 , 38 40 ) and recurrent implantation failure after in vitro fertilization ( 41 ).…”
Section: Associations Of Rs2248374a>g With Human Diseasesupporting
confidence: 73%